Role of the endothelium in the response to cholinoceptor stimulation of rabbit ear and femoral arteries during cooling. - Monge, L. (Nature Publishing Group, 1993)
1. The role of the endothelium in the effects of cooling on the response to cholinoceptor stimulation of the rabbit central ear (cutaneous) and femoral (non-cutaneous) arteries was studied using 2 mm long cylindrical segments. 2. Concentration-response curves for acetylcholine (10(-9)-10(-5) M), methacholine (10(-9)-10(-5) M) and sodium nitroprusside (10(-9)-10(-4) M) were isometrically recorded in arteries under conditions, with and without endothelium or following pretreatment with the nitric oxide-synthesis inhibitor NG-nitro-L-arginine methyl ester (L-NAME, 10(-6)-3 x 10(-4) M) at 37 degrees C and at 24 degrees C (cooling). 3. Ear and femoral arteries showed endothelium-dependent relaxation to acetylcholine and methacholine at 37 degrees C and 24 degrees C. The extent of relaxation of the control ear arteries, but not of the control femoral arteries, to acetylcholine and methacholine increased during cooling. 4. L-NAME (10(-6)-3 x 10(-4) M) reduced in a concentration-dependent way the response of ear arteries to acetylcholine at both 37 degrees C and 24 degrees C, this reduction being more potent at 37 degrees C. L-Arginine (10(-5)-10(-3) M) reversed in a concentration-dependent manner the inhibitor effects of 10(-5) M L-NAME at both temperatures. 5. Sodium nitroprusside caused a concentration-dependent relaxation in both arteries that was endothelium-independent. However, the extent of relaxation to this nitrovasodilator in ear and femoral arteries was lower at 24 degrees C.(ABSTRACT TRUNCATED AT 250 WORDS)